EFFECT OF MALARIA AILMENT ON LABOUR EMPLOYMENT PROBABILITY AND COST IMPLICATIONS IN NIGERIA (2016)
Malaria incidence threatens human existence and reduces economic prospects in countries with high prevalence. Physical challenges caused by malaria can be a limitation to employment probability in the labour market. The co-existence of malaria with high rate of poverty in Nigeria has implications on income loss. While the direct (treatment) and indirect (productivity loss) cost burden of malaria in relation to Gross Domestic Product (GDP) has been examined in Nigeria, its effects on labour employment and income lost to treatment (direct cost) have received little attention. This study, therefore, examined the effect of malaria on employment probability and estimated the cost burden of the illness in terms of income loss. A neoclassical labour supply framework that considered time lost by labour to search for job due to morbidity from malaria was applied. A binary probit model was used to determine the effect of malaria on employment probability. Other factors (age, place of residence, level of educational attainment and gender) that influence the chance of being employed in the labour market were also considered in the model. Data were collected from the 2010 Harmonised Nigerian Living Standard Survey, conducted by the National Bureau of Statistics. Statistical significance was determined at p<0.05. Direct costs were computed using a bottom up approach that summed up the expenditure components (transportation, physician consultation, hospitalisation and drug) of malaria treatment. Income lost to treatment was examined based on the fraction of monthly per capita household income expended as direct cost. This was determined as the ratio of average treatment cost to monthly per capita income earned. Loss in income as indirect cost was determined using the human capital approach that identified persons employed who lost work days due to malaria ailment. An estimate of total income loss in aggregate output was computed as the proportion of total direct and indirect cost in GDP. Malaria ailment significantly reduced employment probability by 78.0% mainly due to inability of labour to search for job while ill. The probability of being employed increased with rise in age between 15-64 years (β=0.01) and urban residency (β=0.07). Employment likelihood fell with increased educational attainment (secondary β= -0.03, tertiary β= -0.04), due to dominance of the informal sector. Males were 6.0% less likely to be employed than females. On average, an individual spent N2, 730 (transportation N470, physician consultation N810, hospitalisation N530 and drug N920) as direct cost (treatment) for an incidence of malaria. This meant that household expenditure for an episode of malaria treatment represented 3% of monthly per capita household income (N91, 000). Indirect cost per incidence of malaria was N34, 040 and N25, 540 for the malaria patient and the caregiver respectively. The total estimated income lost per annum to malaria attack was N1, 906 billion which accounted for 8% of GDP. Malaria ailment reduced employment probability and imposed a huge burden on the economy. Effectively tackling malaria should be prioritized in order to enhance labour employment probability and increase output